Overlooked Realities: Reimagining “Home” and “House” Among Women Domestic Workers in India - Thakkar, Shriya (Violence against women, 2024)
Domestic workers (DWs) are integral to the daily lives of a significant portion of India's urban population, with an estimated 3.9 million individuals employed in domestic roles in urban areas, mostly women. This article explores the perceptions of home, house, and safe spaces among migrant women DWs in Delhi. Through in-depth interviews, it delves into their lived experiences as both breadwinners and survivors of domestic violence, revealing that (a) house and home are differently conceptualized by these workers; (b) their homes are perceived as warzones, reinforcing patriarchy through incidents of domestic violence and gendered subordination; and (c) women DWs navigate the complexities of conflicting identities as breadwinners and survivors within unequal gendered relationships.